Effect of smoking cessation with varenicline on blood pressure control in hypertensive patients. (25th November 2020) - Ioakeimidis, N; Georgakopoulos, C; Emmanouil, E; Dima, I; Solomou, E; Aznaouridis, K; Tousoulis, D; Vlachopoulos, C
Abstract: Purpose: The interaction between smoking and blood pressure (BP) is complex. Despite the strong association between cigarette smoking and cardiovascular disease (CVD) risk, there is paucity about the effect of pharmacotherapies for treating tobacco dependence on BP in already established arterial hypertension. Varenicline has been shown to be an effective and well-tolerated pharmaceutical intervention for smoking cessation. Aim of the study was to investigate the improvement in BP control in smokers with a diagnosis of hypertension who quit or reduced substantially their tobacco consumption by using varenicline and the association of nicotine dependence with BP changes. Methods: A total of 89 (mean age:48±7, 52 males) regular smokers (28±9 pack-years) with a diagnosis of hypertension and on anti-hypertensive drugs were studied. All patients received low-intensity counseling and pharmacotherapy with varenicline (1 mg twice daily) for 12 weeks. Point prevalence smoking abstinence was defined by self-report of complete abstinence in the 7 days before the 12 week clinic visit (end of therapy). Office BP was measured at baseline and each follow-up visit (4 and 12 weeks) office BP. The Fagerström Test for Nicotine Dependence (FTND) was used for assessing nicotine dependence. High nicotine dependence (ND) was defined as a FTND score ≥6. Results: At 12 weeks, 60 (67%) patients were abstinent from smoking and 14 (16%) were non-abstainers who reduced daily consumption to 50% of baseline. The mean time interval between the initiation of treatment with varenicline and smoking abstinence was 1.8±0.6 weeks. There were not significant differences in age, baseline BP level, severity of nicotine dependence and total cigarette consumption (pack-years) between the two groups. Systolic BP (SBP) and diastolic BP (DBP) decreased significantly in abstainers (by 7.2 and 5.5 mmHg at 12 weeks, P<0.01 and P<0.05, respectively) while the decrease in BP level in non-abstainers was minimal. Among patients with sustained tobacco abstinence, 18 were highly ND and 42 had mild and moderate ND. The two ND groups had similar age and BP levels at baseline. Changes in SBP and DBP from baseline in smokers with arterial hypertension between the two ND groups are illustrated in Figure. The observed reductions in SBP and DBP were significant (P<0.05, both for SBP and DBP) when comparing the high ND group to the mild/moderate ND group at 12 weeks. No severe adverse reactions were reported with varenicline use throughout the entire follow-up duration. Conclusion: Varenicline may help smokers with arterial hypertension under antihypertensive therapy to remain abstinent from tobacco cigarette smoking. A novel and important message of this study is also the substantial improvements in office SBP and DBP in highly nicotine dependent sustained tobacco abstainers. Funding Acknowledgement: Type of funding source: None